2019
DOI: 10.38150/sajeb.8(3).p76-82
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of low density polythene-degrading bacteria from soil of North West of Algeria

Abstract: Plas c bags (Low Density Polyethylene (LDPE) belong to the polymers, which plays a very important role in our daily lives by their diversi ed applica on. However, the accumula on of the plas c bags in the environment cons - tutes a serious problem and a real source for visual nuisance, pollu on of soil and marine environments. Furthermore, their biodegradation was the safest method of breakdown that possibly leaves behind less toxic residues and showed poten al of bio-geo chemical cycling of the substrate. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, it can be observed that the respective studies addressed have shown a more significant effect on the degradation of modified plastics such as PS, PE, and PLA, which can be explained by these Satlewal et al, 2008;Sudhakar et al, 2008;Auta et al, 2017Auta et al, , 2018Muhonja et al, 2018;Zerhouni et al, 2018;Maroof et Rajandas et al, 2012;Shimpi et al, 2012;Yoon et al, 2012;Tribedi and Sil, 2013;Taghavi et al, 2021;Tamnou et plastic materials presenting better biodegradability (Chandra and Singh, 2020;Yuan et al, 2020). Initially, the biodegradation of MPs by bacteria occurs from the degradation of larger polymer structures to smaller particles, consequently, degradation into oligomers, dimers, and monomers, finally leading to mineralization through microbial biomass.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, it can be observed that the respective studies addressed have shown a more significant effect on the degradation of modified plastics such as PS, PE, and PLA, which can be explained by these Satlewal et al, 2008;Sudhakar et al, 2008;Auta et al, 2017Auta et al, , 2018Muhonja et al, 2018;Zerhouni et al, 2018;Maroof et Rajandas et al, 2012;Shimpi et al, 2012;Yoon et al, 2012;Tribedi and Sil, 2013;Taghavi et al, 2021;Tamnou et plastic materials presenting better biodegradability (Chandra and Singh, 2020;Yuan et al, 2020). Initially, the biodegradation of MPs by bacteria occurs from the degradation of larger polymer structures to smaller particles, consequently, degradation into oligomers, dimers, and monomers, finally leading to mineralization through microbial biomass.…”
Section: Discussionmentioning
confidence: 95%
“…16S rRNA sequence analysis (1398 bp) indicated 100% similarity to the Bacillus murallis. This strain was identified as an LDPEdegrading bacteria and PE waste-colonizing bacteria in the literature [57,58].…”
Section: Sample 5: Soil Contaminated With Biopolymersmentioning
confidence: 99%